2019
DOI: 10.4067/s2452-45492019000100022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación comparativa en calidad de vida de pacientes con RAUB, RAUBIE vs RAP por cáncer de recto. Informe preliminar

Abstract: The abdominoperineal resection (APR) was the standard treatment of middle-low rectal cancer, in the last 20 years the development of sparing techniques with sphincter preservation with adequate surgical and oncological results has allowed to offer the patient the sphincter apparatus preservation, avoiding the definitive colostomy, however, these techniques may present secondary incontinence to the loss of the rectum. Both surgical options can affect the quality of life of the patient and this element should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…La cirugía continúa siendo parte fundamental del tratamiento. El manejo es una terapia multimodal con baja recurrencia, sin embargo, esta afecta la calidad de (10,25) vida del paciente . Este estudio compara la calidad de vida de los pacientes con CCR tratados con RAP versus resecciones conservadoras de esfínteres: RAB y RAUB.…”
Section: Resultsunclassified
“…La cirugía continúa siendo parte fundamental del tratamiento. El manejo es una terapia multimodal con baja recurrencia, sin embargo, esta afecta la calidad de (10,25) vida del paciente . Este estudio compara la calidad de vida de los pacientes con CCR tratados con RAP versus resecciones conservadoras de esfínteres: RAB y RAUB.…”
Section: Resultsunclassified
“…It demonstrates different realities between these two countries. Also, in the evaluation of 39 Chilean patients with cancer of the medium or low rectum, it was found that the majority (71.8%) had sphincter preservation and only 11 underwent definitive colostomy, with abdominoperineal resection [14].…”
Section: Discussionmentioning
confidence: 99%
“…The abdominoperineal resection is a surgical procedure performed in patients with cancer of the medium or low rectum, in which a definitive colostomy is necessary, as the rectum is amputated, leaving the patient without an anus [14,21].…”
Section: Indications Of Colostomymentioning
confidence: 99%
See 1 more Smart Citation